“Bung Karno” School in the Perspective of Islam in the Archipelago - YASIN, Nur Ali; YAQIN, Mohammad Nurul (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:This study aims to examine the controversy surrounding the statement of "Bung Karno Madzhab" made by Panji Gumilang, a leader of Al-Zaitun Islamic Boarding School in Indramayu. Within the teachings of Ahlussunnah wal Jama'ah, there exists a system of following religious schools of thought, commonly known as madzhab, which generally recognizes four madzhab (Hanafi, Maliki, Shafi'i, and Hanbali). Panji Gumilang's statement about "Bung Karno Madzhab" introduces a new concept that contradicts the Nusantara Islamic traditions, which acknowledges these four madzhab.Methodology:This research utilizes a literature review method with a content analysis approach and a literature study approach to understand Panji Gumilang's statements, public responses, and literature on madzhab in Islam and Islam Nusantara as a representation of Ahlussunnah wal Jama'ah.Findings:The findings of this research indicate that the claim of "Bung Karno's Madzhab" is an act of carelessness and deception, as there is no historical evidence suggesting that Bung Karno established his own madzhab within Islam.Implication:This research provides valuable insights into the implications and understanding of religion related to the controversial statement of "Bung Karno's Madzhab." It serves as a call for the Ahlussunnah wal Jama'ah community in Nusantara to deepen their understanding of Islam critically and comprehensively.